Influence of samarium and iron substitution on structural and electrical properties of barium zirconate titanate solid solutions. Issue 3 (3rd July 2019) - Kaur, Randeep; Singh, Mandeep; Singh, Anupinder
ABSTRACT: Solid solutions of ( x )SmFeO3 -(1- x )Ba(Zr0.05 Ti0.95 )O3 : x = 0, 0.21, 0.22 and 0.23 were synthesized by the solid-state reaction route. Le-Bail analysis of the X-ray diffraction data and Raman spectra revealed the presence of the tetragonal phase ( P4mm space group 99). The remnant polarization ( Pr ) was ~4.08 µC/cm 2 and 1.04 µC/cm 2 for x = 0 and x = 0.21, respectively, while lossy loops were observed for x ≥ 0.22. Canting of the antiferromagnetic spins and ferromagnetic exchange mechanism was responsible for the ferromagnetic feature in the samples. An increase in remnant magnetization ( Mr ) was observed with increases in x . The Nyquist plots revealed the existence of grain and grain boundaries in the overall impedance. Separation of the normalized plots of impedance (Z˝) and modulus (M˝) spectra indicated localized motion of the charge carriers in the sample. The Maxwell–Wagner model fits very well in the low-frequency region ( \~ 10 5 Hz). The ac conductivity obeyed the Universal Jonscher's Power law. The variations in the exponent n suggest that the conduction mechanism conforms to the small polaron hopping mechanism.